2014
DOI: 10.1186/1746-6148-10-122
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic biomarkers correlating with hepatic lipidosis in dairy cows

Abstract: BackgroundHepatic lipidosis or fatty liver disease is a major metabolic disorder of high-producing dairy cows that compromises animal performance and, hence, causes heavy economic losses worldwide. This syndrome, occurring during the critical transition from gestation to early lactation, leads to an impaired health status, decreased milk yield, reduced fertility and shortened lifetime. Because the prevailing clinical chemistry parameters indicate advanced liver damage independently of the underlying disease, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 38 publications
6
74
1
Order By: Relevance
“…We could not detect any differences in fibrinogen con centrations between different degrees of fatty liver, which is not in agreement with recent results (Imhasly et al, 2014) where fibrinogen concentration was nega tively correlated with the degree of lipid infiltration in the liver. Hypofibrinogenemia results from hyperfi brinolysis due to chronic liver disease (Irmak et al, 2006), but can also be associated with DIC in cattle with inflammatory disease (Thomson et al, 1974).…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…We could not detect any differences in fibrinogen con centrations between different degrees of fatty liver, which is not in agreement with recent results (Imhasly et al, 2014) where fibrinogen concentration was nega tively correlated with the degree of lipid infiltration in the liver. Hypofibrinogenemia results from hyperfi brinolysis due to chronic liver disease (Irmak et al, 2006), but can also be associated with DIC in cattle with inflammatory disease (Thomson et al, 1974).…”
Section: Discussioncontrasting
confidence: 38%
“…In cows with LDA, alterations in clotting profiles have been observed and were suspected to be caused by impaired liver function (Irmak and Turgut, 2005;Sobiech et al, 2008). A recent study revealed a negative correlation between plasma fibrinogen concen tration and lipid infiltration in the liver which was at tributed to impaired liver function in advanced liver disease due to lipid infiltration (Imhasly et al, 2014).…”
Section: Laboratory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, very little research has focused on the identification of metabolic biomarkers for poor muscle mass and strength in older adults (11). Here we report the findings of a pilot cross-sectional, nested case-control study using a targeted metabolomics approach, where the concentrations of 180 metabolites belonging to six classes (amino acids, biogenic amines, amino acid metabolites, acyl carnitines, glycerolphospholipids, sphingomyelins, and glucose) were determined by LC MS/MS, using the Biocrates p180 system (15,16). In particular, we contrasted plasma metabolites concentrations between 79 participants with low muscle quality ratio versus 79 controls with high muscle quality who were matched by age, sex, and height.…”
mentioning
confidence: 99%
“…Metabolomics, unlike the other -omics, provides a direct signature of the metabolic state of the organism (12)(13)(14). Recent advances in mass spectrometry allow the simultaneous analysis of hundreds of metabolites from small amounts of biological material (15,16). It is assumed that the biological pathways leading to pathologic conditions causes altered concentrations of specific metabolites and that studying a subset of these metabolites may offer important clues on the pathophysiology of these conditions.…”
mentioning
confidence: 99%